Analisis Kebutuhan Media Pembelajaran Interaktif Biologi pada Siswa SMA Kelas X - Putriyani, Eryzinda Dwigita; Murtini, Iin (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Biology learning at the senior high school level requires the support of interactive learning media to help students understand complex and abstract biological concepts. This study aims to analyze the need for interactive biology learning media among tenth-grade students at SMA Negeri 5 Tuban. A quantitative descriptive method was employed, using non-test data collection techniques in the form of questionnaires and teacher interviews. The instrument was developed using a Guttman scale (Yes/No) consisting of 15 items grouped into three aspects: learning media needs, accessibility and ease of use of learning media, and learning motivation and interest. The subjects of this study were tenth-grade students of SMA Negeri 5 Tuban. Data were analyzed descriptively to determine the level of students’ needs for interactive biology learning media. The results showed that the learning media needs aspect reached 92%, accessibility and ease of use reached 85%, and motivation and learning interest reached 99%, with an overall average of 92%, categorized as a very high level of need. These findings indicate that students have a very high demand for interactive biology learning media, highlighting the importance of developing interactive biology learning materials that align with students’ needs and characteristics.